2021
DOI: 10.3233/faia210296
|View full text |Cite
|
Sign up to set email alerts
|

Soil CEC Predicting Model of Tobacco-Planting Fields in Chenzhou, South Hunan Province

Abstract: Background: Cation exchange capacity (CEC) is a basic but important soil property of soil fertility or quality, CEC predicting model is often derived from other soil properties measured more easily because the traditional method determining CEC is time-consuming and laborious. It is necessary to establish a new CEC prediction model for a new region because CEC predicting model usually is dependent on the study region. Objective: Chenzhou City is the most important and typical tobacco-planting region with tobac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…Lembang and Ciwidey soils have respective pHs of 6.1 and 6.8 which are suitable for garlic growth (Basuki et al, 2019). Many studies showed that the cation exchange capacity (CEC) is an indicator of soil fertility since it depends on organic matter and clay content in soil (AbdelRahman et al, 2022;Bedolla-Rivera et al, 2020;Hailu et al, 2015;Kong et al, 2021;Xiao et al, 2021). The CEC value in Lembang soil was 25.56 (high) higher than in Ciwidey soil with 23.17 (medium), that presumably, garlic grown in Lembang received more nutrients than in Ciwidey soil.…”
Section: The Effect Of G× L Interaction On Yield Charactersmentioning
confidence: 99%
“…Lembang and Ciwidey soils have respective pHs of 6.1 and 6.8 which are suitable for garlic growth (Basuki et al, 2019). Many studies showed that the cation exchange capacity (CEC) is an indicator of soil fertility since it depends on organic matter and clay content in soil (AbdelRahman et al, 2022;Bedolla-Rivera et al, 2020;Hailu et al, 2015;Kong et al, 2021;Xiao et al, 2021). The CEC value in Lembang soil was 25.56 (high) higher than in Ciwidey soil with 23.17 (medium), that presumably, garlic grown in Lembang received more nutrients than in Ciwidey soil.…”
Section: The Effect Of G× L Interaction On Yield Charactersmentioning
confidence: 99%
“…Ogoshi further subdivided the anastomosis group into 18 subgroups of R. solani based on the anastomosis group [18]. The AG-3 anastomosis group, which was rst identi ed and reported to have the widest distribution range on tobacco in China [19]. In another study identi ed the anastomosis group of tobacco target spot pathogens in some tobacco areas of Hunan Province and found that tobacco target spot pathogens belong to R. solani AG-3 anastomosis group [20].…”
Section: Introductionmentioning
confidence: 99%